2011
DOI: 10.1097/psy.0b013e3182303775
|View full text |Cite
|
Sign up to set email alerts
|

Medical Comorbidity of Full and Partial Posttraumatic Stress Disorder in US Adults

Abstract: Objective This study examined associations between lifetime trauma exposures, PTSD and partial PTSD, and past-year medical conditions in a nationally representative sample of U.S. adults. Methods Face-to-face interviews were conducted with 34,653 participants in the Wave 2 National Epidemiologic Survey on Alcohol and Related Conditions. Logistic regression analyses evaluated associations of trauma exposure, PTSD and partial PTSD with respondent-reported medical diagnoses. Results After adjustment for socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(65 citation statements)
references
References 78 publications
3
58
0
Order By: Relevance
“…This result was unexpected because some research has found subthreshold PTSD to be associated with physical health problems. 42 The 95% CI for the HR for the trauma/1–3 symptoms group was wide, however, and included values greater than 1. Further research that assesses all PTSD symptom criteria using a clinical interview is needed to better understand associations of full and partial PTSD diagnoses with CVD.…”
Section: Discussionmentioning
confidence: 99%
“…This result was unexpected because some research has found subthreshold PTSD to be associated with physical health problems. 42 The 95% CI for the HR for the trauma/1–3 symptoms group was wide, however, and included values greater than 1. Further research that assesses all PTSD symptom criteria using a clinical interview is needed to better understand associations of full and partial PTSD diagnoses with CVD.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest the presence of insulin resistance with oral glucose challenge. Although a number of epidemiological studies have found an association between PTSD and diabetes as well as the metabolic syndrome (Lukaschek et al, 2013; Agyemang et al, 2012; Boyko et al, 2010; Goodwin et al, 2005; Pietrzak et al, 2011; Trief et al, 2006; Weiss et al, 2011; Heppner et al, 2009), factors such as medications and co-morbid health conditions may be significant confounders. A unique aspect of this current study is that the subjects are all free of medications, and do not have any chronic medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with PTSD are at increased risk for numerous medical illnesses, including diabetes mellitus (DM), cardiovascular disease, and rheumatoid arthritis (Boscarino, 2004; Weisberg et al, 2002; O’Toole et al, 2007; Bedi et al, 2007). Epidemiological studies have shown that PTSD is associated with a 2–4 fold increased risk of Type 2 diabetes, compared to individuals without PTSD (Lukaschek et al, 2013; Agyemang et al, 2012; Boyko et al, 2010; Goodwin et al, 2005; Pietrzak et al, 2011; Trief et al, 2006). These studies have been conducted in a wide range of samples, including asylum seekers in Europe, veterans in the US, and population based samples of middle-aged and elderly individuals in Germany (Lukaschek et al, 2013; Agyemang et al, 2012; Boyko et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although subthreshold PTSD is associated with both functional impairment and physical conditions (Pietrzak et al, 2011), comorbidity studies have largely focused on those who meet full diagnostic criteria for PTSD. The importance of examining subthreshold PTSD is high, given that PTSD presentations are heterogeneous (Yehuda and McFarlane, 1995), and the specific symptom clusters (e.g., arousal, reexperiencing) linked to physical conditions are unknown.…”
Section: Introductionmentioning
confidence: 99%